2006
DOI: 10.1001/jama.296.4.412
|View full text |Cite
|
Sign up to set email alerts
|

Management of Recalled Pacemakers and Implantable Cardioverter-Defibrillators

Abstract: The decision to replace a device under advisory is determined primarily by the incidence of device malfunction and the likely effects of device failure. This analysis provides a framework for managing recalled devices in the context of device, patient, and institutional characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…In general, for pacemaker-dependent patients, advisory device failure rates in excess of 0.3% warrant consideration of device replacement; in patients with ICD generators under advisory, an estimated failure rate of 3% favors replacement in the majority of cases, decreasing to 1% when procedural mortality rates are 0.1% or less and/or risk of fatal arrhythmias increases to 20% per year. 526 It is anticipated that the above general recommendations and estimates will vary as a function of the specific nature of the advisory, how the malfunction presents, whether early detection and/or reprogramming may be employed in addressing the potential device failure, and whether the lead (versus the generator) is affected. This has been demonstrated, for example, in the case of a recent lead advisory associated with spurious shocks attributable to lead fracture, oversensing, and high impedance; reprogramming to minimize overdetection of noise, enabling of alert features to detect changes in impedance, and increasing utilization of remote monitoring to follow such leads may have an effect on future rates of invasive lead replacement and/or extraction.…”
Section: Elements Of Implantable Cardioverterdefibrillator Follow-upmentioning
confidence: 99%
“…In general, for pacemaker-dependent patients, advisory device failure rates in excess of 0.3% warrant consideration of device replacement; in patients with ICD generators under advisory, an estimated failure rate of 3% favors replacement in the majority of cases, decreasing to 1% when procedural mortality rates are 0.1% or less and/or risk of fatal arrhythmias increases to 20% per year. 526 It is anticipated that the above general recommendations and estimates will vary as a function of the specific nature of the advisory, how the malfunction presents, whether early detection and/or reprogramming may be employed in addressing the potential device failure, and whether the lead (versus the generator) is affected. This has been demonstrated, for example, in the case of a recent lead advisory associated with spurious shocks attributable to lead fracture, oversensing, and high impedance; reprogramming to minimize overdetection of noise, enabling of alert features to detect changes in impedance, and increasing utilization of remote monitoring to follow such leads may have an effect on future rates of invasive lead replacement and/or extraction.…”
Section: Elements Of Implantable Cardioverterdefibrillator Follow-upmentioning
confidence: 99%
“…This finding is in concordance with other studies that have reported a higher risk of infection and other complications from device removal/replacement. 18,19 It is surprising that the risk of complications was not higher for ICDs with cardiac resynchronization therapy as implanting these devices is technically more challenging than implanting regular ICDs; however, our study may not have had enough power to address this question.…”
Section: Discussionmentioning
confidence: 88%
“…3,[12][13][14][15][16] The recent focus on failure rates and related implications for the related leads has focused on patient and system characteristics that influence fracture risk. The Fidelis lead has shown wide variation in survival rate among centers in the manufacturer's CareLink PLUS study (n=21 500 Fidelis leads), implying that there are factors or combinations of factors that are not yet fully understood that result in center to center variation.…”
Section: Discussionmentioning
confidence: 99%